PENCAPAIAN PEMECAHAN MASALAH MATEMATIS SISWA MTsN MELALUI PEMBELAJARAN INQUIRY CO-OPERATION MODEL - Yusup Junaedi; Syahrul Anwar (STKIP La Tansa Mashiro, 2021)
This study aims to determine the achievement of students' mathematical problem solving ability through Inquiry Co- operation Model (ICM) learning, because findings of previous research identified that students still lack the ability to achieve good achievements in mathematics learning. The research method used was a quasi-experimental design with a post-test only control group design. The population in this study were all students of class VIII MTsN in one MTsN in Lebak, Banten Province 2022/2023. The sample selection was conducted randomly against the population class, so that the experimental group is given the treatment of ICM learning and the control group was given the treatment of direct learning. The results showed that: a) as a whole, the achievement of students' mathematical problem solving abilities that obtained ICM learning was higher than students who obtained direct learning; b) based on the high, medium and low KAM categories, the achievement of mathematical problem solving ability of students who obtained ICM learning was higher than students who obtained direct learning with the same KAM category.